Inclusive Practices in Pandemic Times - Olarte, María (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Diversity and educational inclusion are recurring themes in policies, plans and programs, as well as in daily classroom practices; these being guarantors of the participation of all people with equal opportunities. Currently, the health crisis caused by COVID-19 makes it necessary to experiment with dynamics different from those traditionally used in educational processes.  This article focuses on the experiences of teachers and support professionals, with special emphasis on the development of pedagogical practices in inclusion processes during compulsory isolation, using as a methodological perspective the systematization of experiences proposed by Oscar Jara, which allows reconstructing knowledge and resignifying practice as a result of the need for a transformation in the educational space.